Impact of Eimeria meleagrimitis and intermittent amprolium treatment on performance and the gut microbiome composition of Turkey poults - Trujillo-Peralta, Carolina; Latorre, Juan David; Chai, Jianmin; Senas-Cuesta, Roberto; Forga, Aaron; Coles, Makenly; Zhao, Jiangchao; Hernandez-Velasco, Xochitl; Tellez-Isaias, Guillermo; Barta, John; Bielke, Lisa; Hargis, Billy; et al. (Frontiers in Veterinary Science, 2023)
Drug-sensitive live coccidiosis vaccines have been used to control coccidiosis and renew drug sensitivity in commercial chicken operations. However, only limited species coverage vaccines have been available for commercial turkey producers. This study aimed to assess the effect of an E. meleagrimitis vaccine candidate, with and without amprolium intervention, on performance and oocyst shedding. Additionally, the effect of vaccination, amprolium treatment, and E. meleagrimitis challenge on intestinal integrity and microbiome composition was evaluated. Experimental groups included: 1) NC (non-vaccinated, non-challenged control); 2) PC (non-vaccinated, challenged control); 3) VX + Amprol (E. meleagrimitis candidate vaccine + amprolium); and 4) VX (E. meleagrimitis candidate vaccine). For VX groups, 50% of the direct poults were orally vaccinated at DOH with 50 sporulated E. meleagrimitis oocysts and were comingled with contact or non-vaccinated poults for the duration of the study. From d10-14, VX + Amprol group received amprolium (0.024%) in the drinking water. All groups except NC were orally challenged with 95K E. meleagrimitis sporulated oocysts/mL/poult at d23. At d29, ileal and cecal contents were collected for 16S rRNA gene-based microbiome analysis. VX did not affect performance during the pre-challenge period. At d23-29 (post-challenge), VX groups had significantly (P<0.05) higher BWG than the PC group. Contacts and directs of VX groups in LS had significantly reduced compared to PC. As anticipated, amprolium treatment markedly reduced fecal and litter OPG for the VX + Amprol group compared to the VX group which did not receive amprolium. The ileal and cecal content results showed that the PC group had different bacterial diversity and structure, including alpha and beta diversity, compared to NC. Linear discriminant analysis Effect Size (LEfSe) identified that Lactobacillus salivarius (ASV2) was enriched in PC's ileal and cecal content. Compared to NC and PC, the vaccinated groups showed no distinct clusters, but there were similarities in the ileal and cecal communities based on Bray-Curtis and Jaccard distances. In conclusion, these results indicate that vaccination with this strain of E. meleagrimitis, with or without amprolium intervention, caused a very mild infection that induced protective immunity and challenge markedly affected both the ileal and cecal microbiome.